The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Abused women and survivor therapy - Walker, Lenore E. (American Psychological Association, 2006)
Dans ce manuel de traitement de pointe, Lenore E. A. Walker soutient que les psychothérapies traditionnelles pour les victimes de traumatismes ont été insuffisantes pour traiter les femmes maltraitées. Alors que le problème de la violence à l'égard des femmes continue de tourmenter la société, couvrant tous les secteurs démographiques, Walker décrit des modifications essentielles à la pratique traditionnelle qui permettront aux praticiens de travailler plus efficacement avec les femmes victimes de violence. Ces modifications aboutissent à une compilation intégrée des stratégies d'évaluation et d'intervention les plus réussies, appelées « thérapie de survivant ». La thérapie des femmes maltraitées et des survivants discute des principales formes de violence subies par les femmes : viol et agression sexuelle, coups de feu, abus sexuels commis par des thérapeutes et discrimination/harcèlement sexuel sur le lieu de travail. Walker examine les effets du sexe, de la race, de l'ethnicité, de la culture et de l'orientation sexuelle sur chaque forme d'abus ; discute des considérations cliniques et des approches de traitement ; évalue les instruments d'évaluation couramment utilisés ; et analyse les problèmes médico-légaux dans les cas impliquant la violence contre les femmes. Walker soutient que les modèles de traitement réussis doivent tenir compte de l'impact spécifique des diverses formes d'abus, de la réponse psychologique unique de l'individu au monde, de l'impact de la socialisation traditionnelle des femmes et des hommes, et du transfert de thérapeutes et du contre-transfert. Ces considérations peuvent être appliquées au cours d'une thérapie qui cherche à réautonomiser les femmes maltraitées en les aidant à retrouver leur estime de soi, à rétablir des relations saines et à retrouver un sentiment de contrôle et de choix dans leur vie. La thérapie des femmes maltraitées et des survivants aide les praticien.nes nouvellement formé.e.s ainsi que le praticien.ne expérimenté.e à identifier, évaluer et traiter les femmes qui ont été maltraitées physiquement, sexuellement ou psychologiquement.
Keywords: approches et analyses; cours; discipline; intersectionnalité; psychologie; santé; santé mentale; sciences humaines; thématiques; traumatismes; trs3500; violences; violences conjugales; violences sexuelles

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis